FEATURES OF ADAPTATION TO INTENSIVE PHYSICAL LOAD OF SKILLED CYCLISTS SPECIALIZING IN MOUNTAIN BIKE - Kvashuk, P.V.; Voronov, A.V.; Semaeva, G.N.; Malkin, R.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the features of the adaptation of the neuromuscular apparatus and vegetative functions to physical activity of progressively increasing power and the mechanisms for maintaining the performance of qualified cyclists specializing in mountain biking. Methods and structure of the study. The work was attended by five cyclists of CMS and MS qualifications, specializing in mountain biking (MTB). As a model testing load, a standard stepwise test was used, performed to “failure”. The test load was performed on an ELITE bike machine, REAL-TURBO-MUIN model (Italy). Results and conclusions. This study shows that, along with additional activation of presumably fast muscle fibers at a power of 75-80% max, an effective mechanism for maintaining the special performance of qualified cyclists is the level of intermuscular coordination, which provides synergism in the work of the thigh and lower leg muscles with a further increase in pedaling power.